Nursing Care in Complex Congenital Heart Disease and Respiratory Distress Syndrome for Baby in NICU - Maulida Dwi Yani; Nova Fajri; Nenty Septiana (Chakra Brahmanda Lentera Institute, 2023)
Background: Neonates are at high risk for health problems. Without proper treatment, those problems might lead to either disability or death. Congenital heart disease causes respiratory distress syndrome (breathing distress syndrome), with symptoms of dyspnea, cyanosis, and respiratory arrest due to pathological changes in the heart that disrupt the blood flow cycle throughout the body. This study aimed to discover nursing care for Baby MH with complex congenital heart disease and respiratory distress syndrome. Methods: This research used a case study design—data collection from assessment to evaluation in the NICU in December 2022. The patient was observed for 4 days. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis was carried out using narrative analysis. Results: Baby MH looks dyspnea with minimal epigastria retraction and hypersecretion in the mouth with CPAP installed. The nursing diagnoses in the case of Baby MH are ineffective breathing patterns, decreased cardiac output, activity intolerance, risk of shock, risk of hypothermia, risk of developmental disorder, and risk of attachment disorders. The interventions provided are based on the Indonesian Nursing Intervention Standards, consisting of observational, therapeutic, and collaborative interventions. Conclusion: Nursing problems in baby MH after the treatment showed that the problem of ineffective breathing patterns had not been resolved, but the decreased cardiac output was partially handled while the activity intolerance had not been resolved. However, no shock occurred, and the risk of hypothermia was partially resolved.